Characteristic Modes Analysis of Aperiodic Arrays Using Entire Domain Basis Function Method With Adaptive Cross Approximation Algorithm - Zhang, He-Qing; Du, Ping; Zhu, Song-Song (IEEE antennas and wireless propagation letters, 2023)
The characteristic modes of the aperiodic arrays are analyzed by combining the entire domain basis function method with the adaptive cross approximation (ACA) algorithm. The array cells are identical. The entire domain basis functions defined on the array cells are obtained by analyzing the characteristic modes of the reference cell firstly. Then, the generalized eigenvalue equation whose size is smaller than the conventional one can be obtained. After solving the equation, the characteristic modes of the whole array can be analyzed. Calculation of the matrices is very time-consuming. To speed up the computation, the ACA algorithm is applied. Several numerical examples are performed. The accuracy and computational efficiency of the proposed technique are validated by simulation results.